Using GIS to Record and Analyse Historical Urban Areas - Maria Giannopoulou; Athanasios P. Vavatsikos; Konstantinos Lykostratis; Anastasia Roukouni (TeMA: Journal of Land Use, Mobility and Environment, 2014)
A significant part of the cultural heritage of towns and cities worldwide is the built heritage. The historic centre of several European cities has been preserved as an important part of the urban landscape. New analytical tools and concepts are thus required, which would enrich and expand the conventional methods and achieve sustainability of cultural heritage in any urban context, among which are Geographical Information Systems (GIS), digital mapping systems that link spatial and non – spatial data of landscape features, and can contribute substantially in documenting different urban features and furthermore in modelling the urban process and its impact on heritage regions. This paper is part of a wider research still in progress and refers to the creation of a specialised GIS, which includes a great range of geometric and descriptive information that can be used for the interpretation, monitoring, visualisation and evaluation of urban heritage areas. The case study of the paper is the Old Town of Xanthi, one of the most important examples of the 19th century’s urban civilization in Northern Greece. The paper focuses on the elaboration of the data concerning the built environment and more precisely to its systematic retrieval and import to the GIS system; moreover it examines 17 chosen variables using a combination of Multivariable analysis methods (Correspondence and Hierarchical Cluster Analysis). The analysis has shown the existence of four distinctive and very interesting groups which have their own specific characteristics. Ideas for further research include the collaboration with specialised sophisticated software which would facilitate the thorough examination, analysis and correlation of parameters involved, towards the principles of sustainable and smart city development. A significant part of the cultural heritage of towns and cities worldwide is the built heritage. The historic centre of several European cities has been preserved as an important part of the urban landscape. New analytical tools and concepts are thus required, which would enrich and expand the conventional methods and achieve sustainability of cultural heritage in any urban context, among which are Geographical Information Systems (GIS), digital mapping systems that link spatial and non – spatial data of landscape features, and can contribute substantially in documenting different urban features and furthermore in modelling the urban process and its impact on heritage regions. This paper is part of a wider research still in progress and refers to the creation of a specialised GIS, which includes a great range of geometric and descriptive information that can be used for the interpretation, monitoring, visualisation and evaluation of urban heritage areas. The case study of the paper is the Old Town of Xanthi, one of the most important examples of the 19th century’s urban civilization in Northern Greece. The paper focuses on the elaboration of the data concerning the built environment and more precisely to its systematic retrieval and import to the GIS system; moreover it examines 17 chosen variables using a combination of Multivariable analysis methods (Correspondence and Hierarchical Cluster Analysis). The analysis has shown the existence of four distinctive and very interesting groups which have their own specific characteristics. Ideas for further research include the collaboration with specialised sophisticated software which would facilitate the thorough examination, analysis and correlation of parameters involved, towards the principles of sustainable and smart city development.